Skeletal Muscle Mitochondrial Dysfunction and Oxidative Stress in Peripheral Arterial Disease: A Unifying Mechanism and Therapeutic Target - Kyoungrae Kim; Erik M. Anderson; Salvatore T. Scali; Terence E. Ryan (MDPI AG, 2020)
Peripheral artery disease (PAD) is caused by atherosclerosis in the lower extremities, which leads to a spectrum of life-altering symptomatology, including claudication, ischemic rest pain, and gangrene requiring limb amputation. Current treatments for PAD are focused primarily on re-establishing blood flow to the ischemic tissue, implying that blood flow is the decisive factor that determines whether or not the tissue survives. Unfortunately, failure rates of endovascular and revascularization procedures remain unacceptably high and numerous cell- and gene-based vascular therapies have failed to demonstrate efficacy in clinical trials. The low success of vascular-focused therapies implies that non-vascular tissues, such as skeletal muscle and oxidative stress, may substantially contribute to PAD pathobiology. Clues toward the importance of skeletal muscle in PAD pathobiology stem from clinical observations that muscle function is a strong predictor of mortality. Mitochondrial impairments in muscle have been documented in PAD patients, although its potential role in clinical pathology is incompletely understood. In this review, we discuss the underlying mechanisms causing mitochondrial dysfunction in ischemic skeletal muscle, including causal evidence in rodent studies, and highlight emerging mitochondrial-targeted therapies that have potential to improve PAD outcomes. Particularly, we will analyze literature data on reactive oxygen species production and potential counteracting endogenous and exogenous antioxidants.